2015 IEEE 2nd International Conference on Cybernetics (CYBCONF) 2015
DOI: 10.1109/cybconf.2015.7175981
|View full text |Cite
|
Sign up to set email alerts
|

Bag-of-features image indexing and classification in microsoft SQL server relational database

Abstract: Abstract-This paper presents a novel relational database architecture aimed to visual objects classification and retrieval. The framework is based on the bag-of-features image representation model combined with the Support Vector Machine classification and is integrated in a Microsoft SQL Server database.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Various implementations of descriptors aggregation following artificial neural networking classification are also known. The approach based on the bag of features build from image SIFT keypoint descriptors following by k-means clustering and SVM classification was introduced in [6]. The numerical results in this research showed that selection of quantity of words in the dictionary for BOW model should be a responsible choice as its increasing could make results worser.…”
Section: Related Workmentioning
confidence: 94%
“…Various implementations of descriptors aggregation following artificial neural networking classification are also known. The approach based on the bag of features build from image SIFT keypoint descriptors following by k-means clustering and SVM classification was introduced in [6]. The numerical results in this research showed that selection of quantity of words in the dictionary for BOW model should be a responsible choice as its increasing could make results worser.…”
Section: Related Workmentioning
confidence: 94%